Peer Influence and Single Parenting as Predictors of Sexual Abuse Among Secondary School Students in Nigeria - Martins, Igbineweka Noyosase; Omogbai, Edith Omorionmwen (International Journal of Applied Guidance and Counseling, 2024)
This study examined peer influence and single parenting as predictors of sexual abuse among secondary school students in Ovia North East Local Government Area of Edo State, Nigeria. Two research questions were raised and two hypotheses were formulated. The correlational survey research design was used for the study. The population of the study is Eleven thousand nine hundred and eighty-five (11985) senior secondary school students in the public and private schools in Ovia North East Local Government Area. The multistage sampling procedure was employed to select 300 students from six (6) senior secondary schools in Ovia North East Local Government Area. The research instrument was a questionnaire titled " Single Parenting, Peer Influence, and Sexual Abuse Questionnaire Scale " was used for the study. The data was analysed using inferential statics (Linear Regression and t-test). It was shown from the findings that peer influence and single parenting both significantly predict sexual abuse amongst secondary school students (p<0.05) and also established that there is a significant difference between public and private schools in their disposition to sexual abuse among secondary school students in Ovia North East Local Government Area of Edo State (T-cal>1.96 & p<0.05). Given the outcome of this study, it was recommended that seminars should be organized for students due to the dangers of indecent dressing and premarital sex, secondary schools should ensure that they have an operational counselling centre and specialised counsellors who can organise individual and group counselling sessions for victims of sexual abuse.